Nephrogenic factors of resistance to antihypertensive treatment in patients with essential hypertension - N. V. Teplova; V. A. Lyusov; R. G. Oganov; E. M. Evsikov; R. A. Sharipov; M. H. Zhapoeva; E. G. Kurumlidu (Столичная издательская компания, 2015)
Aim. To study the prevalence of renal and renovascular disorders in the development and progression of primary arterial hypertension (HT) resistant to combination antihypertensive therapy (AHT) in cardiac and therapeutic patients of general hospital. Material and methods. 286 patients with essential HT stages 1-3, including 105 patients with stages 2-3 with the signs of treatment resistance were included into the study. All patients were treated with personalized AHT in accordance with current guidelines for the management of HT. Laboratory and instrumental assessment of a functional status of kidneys was performed. Results. A group of patients with resistant HT made 36.7% of the total number of examined patients. The most significant distinction in patients with resistant HT was a high incidence of changes in renal vessels and infrarenal aorta. Deformation of the abdominal aorta (9.7%), renal arteries tortuosity (7.3%), vasourethral conflict (4.8%) were detected in this group significantly more often. Conclusion. Congenital and acquired lesions of renal arteries are detected several times more often in patients with resistant essential HT.